Le droit québécois et les troubles musculo-squelettiques : règles relatives à l’indemnisation et à la prévention - Katherine Lippel (Perspectives Interdisciplinaires sur le Travail et la Santé)
In Québec, musculo-skeletal disorders (MSDs) are a significant source of work related disability and constitute the majority of lost time claims for occupational disease. For every MSD compensated as an occupational disease, between 5 and 6 such claims are accepted as resulting from work accidents. Québec workers’ compensation legislation allows for compensation either as an occupational disease or as a work accident, but in either case this type of claim is frequently the subject of contestation. This article examines the evolution of the legal framework governing access to workers’ compensation for this type of occupational injury and also examines the principle legal mechanisms empowering occupational health and safety (C.S.S.T.) inspectors. The C.S.S.T., is responsible for the implementation of both the workers’ compensation scheme and the prevention mechanisms provided for in the occupational health and safety legislation. The article concludes with a brief survey of recent regulatory developments with regard to ergonomic standards enacted in other Canadian jurisdictions for the purpose of the prevention of MSDs.